Gastroduodenal Intussusception, Intermittent Biliary Obstruction and Biochemical Pancreatitis due to a Gastric Hyperplastic Polyp - Elie Chahla; Michael A. Kim; Brandon T. Beal; Samer Alkaade; Robert W. Garrett; Louay Omran; Michael T. Ogawa; Jason R. Taylor (Case Reports in Gastroenterology, 2014)
We present the case of a 76-year-old man with gastroduodenal intussusception secondary to a gastric hyperplastic polyp. Intussusception in the adult population occurs infrequently. Our patient presented with gastroduodenal intussusception, which is very uncommon and accounts for <10% of all types of intussusception. This case is unique in that partial endoscopic resection of the gastric hyperplastic polyp resolved the patient's gastroduodenal intussusception, biliary obstruction and biochemical pancreatitis without the need for surgical intervention.